PENGEMBANGAN KOMPETENSI BAGI GURU SMPN 22 PADANG DALAM MATERI PEMBELAJARAN SENI RUPA - Lisa Widiarti; Eliya Pebriyeni (Ranah Seni, 2019)
The implementation of art education in public schools, especially at the level of secondary education, must be based on the principle that art education is an educational vehicle and builds student creativity. Orientation of Art and Culture / Fine Art subjects in junior high schools is to facilitate emotional, intellectual, physical, conception, social, aesthetic, artistic and creativity experiences for students by conducting creative and creative activities on various products around students that are beneficial to human life. The selection of the right media in creating art for students is the right thing for the creation of creative works and will also make students more interested in learning and will be fun. But in practice, the subject of Cultural Arts is often replaced with other subjects because many teachers do not master the Culture and Arts learning material. The reality in the field, especially learning in the field of Fine Arts and skills, is confronted with various problems, including the quality of the expertise of the teaching staff and the learning time at each meeting in a very short class. This makes it difficult for teachers to finish the material outlined by GBPP: and ultimately results in the problem of learning material being confused because it is often changing. PKM is focused on training the teacher in the matter of mastery of the material and alternative materials that can be used for practicum in Fine Arts learning. One of the efforts in the development of media for work that is fun for students is to make 3-dimensional calligraphy works of paper pulp. In this case the teachers will be taught how to utilize used paper material that is processed into paper pulp, to make mummy or applied artwork that is relatively easy to teach to junior high school students and relatively requires a relatively short amount of time. The determination of priority issues is carried out jointly between the Implementation Team and the Partner Leaders. Problem solving is done by the method: (1) lectures, (2) demonstrations / demonstrations, and (3) training with the guidance of the instructors and ends with questions and answers. The target activity output targets are: (1) publishing training articles (2) increasing partner teacher understanding of understanding, techniques and processes that are quite simple in utilizing pulp, and (3) producing products / works: at least each participant produces two or three Fine art works in the form of 3-dimensional calligraphy.